2016
DOI: 10.1073/pnas.1519881113
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus receptor switch explained from the stereochemistry of protein–carbohydrate interactions and a single mutation

Abstract: Hemagglutinin-esterases (HEs) are bimodular envelope proteins of orthomyxoviruses, toroviruses, and coronaviruses with a carbohydrate-binding "lectin" domain appended to a receptordestroying sialate-O-acetylesterase ("esterase"). In concert, these domains facilitate dynamic virion attachment to cell-surface sialoglycans. Most HEs (type I) target 9-O-acetylated sialic acids (9-O-Ac-Sias), but one group of coronaviruses switched to using 4-O-Ac-Sias instead (type II). This specificity shift required quasisynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 58 publications
5
66
0
Order By: Relevance
“…3A). This may be due to stabilization of the interaction at low temperature, as was previously described for several other Sia-binding viruses (19,20). NA treatment of several cell types revealed that Sia supports CV-A24v infection of HCE and HAP1 cells, but not of HeLa cells (Fig.…”
Section: Resultssupporting
confidence: 65%
“…3A). This may be due to stabilization of the interaction at low temperature, as was previously described for several other Sia-binding viruses (19,20). NA treatment of several cell types revealed that Sia supports CV-A24v infection of HCE and HAP1 cells, but not of HeLa cells (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Only a single study showed that the ability of NA to bind red blood cells corresponded to the cleavage efficiencies of other multivalent substrates (26). Enhancement of catalytic efficiency resulting from catalytic and carbohydrate-binding domains interacting simultaneously with a polyvalent substrate appears to be a general feature of most glycoside hydrolases, as most of these enzymes have been shown to contain lectin domains, including eukaryotic and bacterial NA proteins (44), as well as other viral-receptordestroying enzymes (45,46). The 2nd SIA-binding site, which is adjacent to the actual NA active site, may enhance the catalytic efficiency of NA by recruiting and keeping multivalent sialosides close to the active site (26,43).…”
Section: Discussionmentioning
confidence: 99%
“…2A) (Hulswit et al, 2019;Tortorici et al, 2019). This site is conserved in all other CoVs known to attach to 9-O-Ac-Sia (β-CoVs, lineage A) and shares architectural similarity with the ligand-binding pockets of CoV hemagglutinin-esterases and influenza virus C/D hemagglutinin-esterase-fusion glycoproteins, highlighting common structural principles of recognition (Bakkers et al, 2017(Bakkers et al, , 2016 Hulswit et al, 2019;Rosenthal et al, 1998;Tortorici et al, 2019). The current consensus in the field is that HCoV-OC43 only utilizes 9-O-Ac-sialosides as host receptors.…”
Section: Diversity Of Cov Receptors and Entry Mechanismsmentioning
confidence: 99%
“…The CoV virion contains at least four structural proteins: spike (S), envelope (E), membrane (M) and nucleocapsid (N). In contrast to other β-CoV lineages, lineage A CoVs also encode a hemagglutinin-esterase which serves as receptor-destroying enzyme to facilitate release of viral progeny from infected cells and escape from attachment to non-permissive host cells or decoys (Bakkers et al, 2017(Bakkers et al, , 2016. S is a class 1 viral fusion protein that promotes host attachment and fusion of the viral and cellular membranes during entry (Bosch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%